(untitled) (The Journal of Forensic Accounting Profession, 2023)
In today’s increasingly connected and digitized business environment, brands face numerous challenges that can significantly affect their reputation and value, and one of the key challenges that many organizations across the world face is brand risk. Due to its role in many aspects of business, the main purpose of this paper is to revitalize this phenomenon by exploring it through bibliometric indicators, publishing trends and analyzing it through the current literature. In this sense, the paper adresses two research questions, both related to revealing the scope and nature of brand risk as the construct of a great relevance in many scientific fields, whereas a special attention has been given to the analysis of the most cited papers on this matter. The findings show that the construct although presented two decades ago is still in infancy phase, and quite neglected in the current body of knowledge. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2023-0005, pod licencom CC BY-NC-ND 4.0)